The Role of Homoeopathic Constitutional Remedies in Cases of Infertility (Advancements in Homeopathic Research, 2022)
This study shows that Homoeopathic constitutional remedies remove the miasmatic obstructions leading to infertility and successfully manage the cases. Those remedies also enhance the positive actions of allopathic medicines, when given after a dose of constitutional remedy. Almost 60% ( 18/ 30) cases show conception naturally within 6 months following constitutional homoeopathic remedy alone. But 26.66% (8/ 30) cases show conception with repeat use of clomiphene citrate or IUI 3 months later homoeopathic constitutional remedy, which fails to occur with same before homoeopathic support. And 13.33% ( 4/30) cases fail to conceive and need further investigations and management like laparoscopy or IVF. Overall outcome of this clinical study is encouraging and unique to all the medical fraternity.
Keywords: Infertility; Homoeopathic; Remedies; Constitution